2015
DOI: 10.1108/ijchm-06-2013-0237
|View full text |Cite
|
Sign up to set email alerts
|

Pricing strategies for resort fees: consumer preferences favor simplicity

Abstract: Purpose – The purpose of this study is twofold: to determine hotel customers’ preference among hotel amenities pricing strategies, specifically a bundled, all-inclusive charge in the form of a resort fee, a limited choice resort fee at a lower price or a la carte pricing, and to determine whether hotel customer prefer bundled or partitioned pricing when faced with a mandatory resort fee. Design/methodology/approach – An online survey of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 28 publications
0
14
1
Order By: Relevance
“…Correspondingly, the shorter the stay of a resident in the dormitory, the higher the probability that he will prefer a bundled fee. Contrary to the findings in the hospitality industry of the study conducted by Repetti et al (2015), the customers in the accommodation sector preferred a partitioned fee over a bundled fee or a limited choice fee. This preference is inconsistent with the pricing strategy employed by most dormitories across multiple countries.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Correspondingly, the shorter the stay of a resident in the dormitory, the higher the probability that he will prefer a bundled fee. Contrary to the findings in the hospitality industry of the study conducted by Repetti et al (2015), the customers in the accommodation sector preferred a partitioned fee over a bundled fee or a limited choice fee. This preference is inconsistent with the pricing strategy employed by most dormitories across multiple countries.…”
Section: Discussioncontrasting
confidence: 99%
“…Hence, it is critical for both managers and customers to understand the reasoning of pricing strategies in this industry. Repetti et al (2015) found that hotel consumers prefer bundled pricing over partitioned pricing in a report of 2 to 1, favoring the former. Similar findings are reached by Bambauer and Gierl (2008) in a study about purchasing decisions in commerce.…”
Section: Research Questions and Hypothesismentioning
confidence: 99%
See 2 more Smart Citations
“…Bundling, a commonplace marketing method, involves selling two or more products/services in a package, oftentimes for a special price (Adams and Yellen 1976;Guiltinan 1987). Examples of bundled products in the hospitality and tourism industries include combined restaurant meals, hotel amenities, and travel packages (Kim, Bojanic, and Warnick 2009;Kwon and Jang 2011;Repetti, Roe, and Gregory 2015). Bundled travel products such as accommodation and transportation are particularly prevalent in online travel intermediaries (OTAs; Kim, Bojanic, and Warnick 2009;Tanford, Baloglu, and Erdem 2012).…”
Section: Bundling In the Travel Industrymentioning
confidence: 99%